PERANAN BADAN KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN DALAM MENGIMPLEMENTASI PROGRAM KB PRIA (MOP) DI KABUPATEN KAMPAR TAHUN 2013 - Novri Yenti; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the role of Family Planning Agency and Women's Empowerment in implementing the family planning program in Kampar regency Gentlemen. As for the background of this research is not yet achieved the target of family planning acceptors Men in Kampar regency and the condition of the lack of information about family planning in Kampar regency Gentlemen. This study uses a qualitative method of data collection techniques by means of in-depth interviews and the use of libraries as well as qualitative descriptive data analysis. The necessary data, among others; primary data obtained through interviews and secondary data obtained through library research on issues related to this study. Based on the survey results revealed that the role BKBPP Kampar district in implementing the family planning program is to make efforts male socialization and continuous coordination with Government agencies, but to socialize Men specific family planning program is not yet done. The factors that affect BKBPP in implementing the family planning program of Men is a factor of limited human resources, limited means of supporting and budget constraints factorKeywords : Implementation, MOP, Role , Agencies